The Effect of Career Development, Self-Efficacy and Non-Physical Work Environment on Employee Job Satisfaction - Sugianti, Evi Oktobriana; Hartono, Sri; Rapini, Titi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to identify the influence of career development, self-efficacy and non-physical work environment on job satisfaction of employees of PT BPRS Mitra Mentari Sejahtera Ponorogo. This type of research is a survey. The research subjects were 50 employees. This data was collected by questionnaire and analyzed using multiple linear regression analysis. The results showed that: 1) career development has a negative effect on employee job satisfaction with a t count value of -0.211 < t table 2.01290 with a significant 0.834. 2) self-efficacy has a significant positive effect on employee job satisfaction with a t count value of 2.506> t table 2.01290 with a significant 0.016. 3) Non-physical work environment has a significant positive effect on employee work discipline with a t count value of 3.572> t table 2.01290 with a significant 0.001. 4) Leadership, compensation, and work environment simultaneously affect employee work discipline with an F count value of 22.616> F table 2.81 with a significant 0.000. The contribution of leadership, compensation and work environment has a positive effect on employee work discipline by 59.6%. The regression equation obtained is Y = 1 - 0.027 X1 + 0.264 X2 + 0.439 X3 + e